DIFFERENTIAL DIAGNOSIS OF THE PROLIFERATIVE FORM OF LEUKOPLAKIA IN PATIENTS WITH DIABETIC IMMUNODEFICIENCY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The proliferative form of oral leukoplakia in patients with type 2 diabetes mellitus and secondary immunodeficiency is characterized by extensive epithelial hyperplasia, persistent keratinization, and an increased risk of malignant transformation. This study examines the morphological and cytological criteria required for its differential diagnosis, particularly in comparison with oral manifestations of lichen planus and lupus erythematosus. Clinical evaluation in immunocompromised diabetic patients frequently reveals thickened white plaques with sharply defined borders, resistant to mechanical removal and predominantly localized to trauma-prone areas. Histological analysis identifies marked hyperkeratosis, acanthosis, parakeratosis, and a polymorphic inflammatory infiltrate, including segmented neutrophils and plasma cells within the lamina propria. The presence of epithelial dysmaturation with loss of nuclear polarity, cytoplasmic eosinophilia, and intercellular edema further delineates the proliferative variant. In contrast to the lichenoid pattern of T-cell-mediated basal vacuolization in lichen planus and the perivascular collagen degeneration in lupus erythematosus, proliferative leukoplakia exhibits reactive epithelial remodeling driven by local mechanical and systemic metabolic factors. Cytological smears confirm the prevalence of keratinized cells with nuclear atypia and a reduction in intermediate epithelial elements. The findings validate the diagnostic framework necessary for identifying high-risk keratotic lesions in diabetic individuals under immunosuppressive conditions.